Mechanochemical preparation of molecular and ionic co-crystals of the hormone melatonin. Issue 18 (17th April 2019) - Shemchuk, O.; André, V.; Duarte, M. T.; Braga, D.; Grepioni, F.
Abstract : Molecular and ionic co-crystals of melatonin with piperazine, DABCO and CaCl2 were obtained via kneading with ethanol: the solubility of melatonin in H2 O increases by an order of magnitude when combined with CaCl2 . Abstract : Two co-crystals of melatonin with piperazine and (1, 4-diazabicyclo[2.2.2]octane), DABCO, and a hydrated ionic co-crystal with CaCl2 were obtained directly in the solid-state via kneading of the solid mixtures with a few drops of ethanol. The structure of the DABCO co-crystal, mel2 ·DABCO, was determined by single crystal X-ray diffraction, while those of the piperazine co-crystal, mel2 ·pip, isomorphous with the DABCO one, and the ionic co-crystal, mel2 ·CaCl2 ·2H2 O, were determined from powder data. In the case of the ionic co-crystal with CaCl2, solubility measurements indicate that melatonin solubility in water increases by an order of magnitude with respect to the pure substance.